A two-stage observer for the compensation of actuator-induced disturbances in tool-force sensors. (1st January 2021) - Knechtelsdorfer, U.; Saxinger, M.; Schwegel, M.; Steinboeck, A.; Kugi, A.
Highlights: Tool-force measurements are often deteriorated by the motion and inertia of the tool. A combined observer strategy is developed to compensate this measurement error. Part 1 of the observer estimates the steady-state actuator behavior by least squares. Part 2 estimates an unknown disturbance force by a reduced Luenberger observer. Abstract: In this paper, a novel two-stage observer strategy for improving the measurement of tool forces is presented. The mass-spring-damper system which inevitably occurs when a tool and a (compliant) force sensor are combined is studied and its adverse influence on the measurement signal is analyzed. The proposed observer consists of two stages. The first stage captures the input-output characteristics from the control input to the tool force by a recursive least-squares estimation algorithm. The estimated tool characteristics are used in a second stage to suppress the oscillations in the measurement signal, which mainly occur due to the mass-spring-damper nature of the tool-sensor combination. In a tailored experimental test rig, which mimics the conditions in magnetic levitation, magnetic bearings, or magnetic strip positioning devices in hot-dip galvanizing lines, the efficacy and the high estimation accuracy of the developed observer strategy are demonstrated.